Preliminary research on the presence of viruses and parasites in the Lake of Valencia and its tributary rivers - Botero de Ledesma, Ligia; García de Hurtado, María Cristina (Rev. Téc. Fac. Ing. Univ. Zulia)
The reusability of waters with agricultural and industrial aims is a necessity, due to the increasing demand for water and the shortage of this vital resource. The Lake of Valencia, located in the Central Region of the country, in one of the most populated areas in Venezuela, it is a reservoir of fresh water, that is expected, to be used in agriculture, sporting activities or as an alternative water supply for the cities located in its river basin. The reuse of this water can cause problems for public health, since the lake receives water from several rivers that receive residual water discharge from the populations located along them, which could contain pathogenic microorganisms. In order to determine the microbiological quality of this water, and to permit the formulation of active microorganism control policies, samplings in five zones of the Lake and its tributary rivers were made, to detect virus and parasites. Microorganisms were determined following standards techniques, that demonstrated that in three of the zones of the Lake and in its tributary rivers, there was presence of enteric virus, bacteriophage and Giardia. The other two zones resulted negative the first year and positive the second year, when the volume of the sample processed was increased. The results demonstrate a high microbial contamination in this reservoir and the necessity to give lake water adequate treatment before using it as drinking water.